2009
DOI: 10.4085/1062-6050-44.6.630
|View full text |Cite
|
Sign up to set email alerts
|

Athletic Training Approved Clinical Instructors' Reports of Real-Time Opportunities for Evaluating Clinical Proficiencies

Abstract: Most clinical proficiencies are evaluated via simulations. The ACIs should maximize real-time situations to evaluate students' clinical proficiencies whenever feasible. Athletic training education program administrators should develop alternative methods of clinical proficiency evaluations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 16 publications
(38 reference statements)
0
28
1
Order By: Relevance
“…29,30 The use of simulations or scenarios to evaluate student learning and skill proficiency has become increasingly popular among ATEPs 31,32 because real-life opportunities often are limited, 29,30 particularly with medical emergency conditions such as EHS. The simulations discussed by our group of participants were informal and a means to create discussions among peer groups rather than to stimulate critical thinking or skill development because the students were not instructed to implement the skills but rather to speak hypothetically.…”
Section: Doug Echoed Those Concernsmentioning
confidence: 99%
“…29,30 The use of simulations or scenarios to evaluate student learning and skill proficiency has become increasingly popular among ATEPs 31,32 because real-life opportunities often are limited, 29,30 particularly with medical emergency conditions such as EHS. The simulations discussed by our group of participants were informal and a means to create discussions among peer groups rather than to stimulate critical thinking or skill development because the students were not instructed to implement the skills but rather to speak hypothetically.…”
Section: Doug Echoed Those Concernsmentioning
confidence: 99%
“…Specifically, research has demonstrated the need for realistic learning opportunities in a safe, low-risk environment that engage critical thinking and clinical decision-making. 14,[39][40][41] Through the creation of a realistic clinical scenario used in both the CBL and the HS, we found the ability to provide realistic, low-risk teaching opportunities. The HS method provided hands-on opportunities and allowed for real-time clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…6 Preceptors are expected to create an effective learning environment at their clinical site with intentions to prepare the P-ATS for independent clinical practice, yet some authentic patient encounters and day-today tasks may not be possible because of the nature of the clinical site. 2,7 As such, P-ATSs report clinical deficiencies in areas with minimal opportunities for meaningful encounters such as health care administrative tasks during their transition to practice. 8,9 Previous research has identified that preceptors in athletic training turn to simulations when real-time opportunities are not available to assess P-ATSs' abilities to meet their current curricular content standards.…”
Section: Introductionmentioning
confidence: 99%